ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYEDIAAN DAN PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH DI KOTA PEKANBARU - Simbolon, Joni Pranata; ', Gusnardi; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: one of the main factors resulting in difficulty and failure for the small and medium enterprises to expand thei business is incapability in accounting. The researcher conducted a study of factors influencing on accounting information at the small and medium enterprise in Pekanbaru City. Variable used in this research is manajer/owner’s educational background, business size, the manager/owner’s length of time in managing, business age, training on accounting, and application and the available of accounting information. The objective of this study was to provide empirical evidence of the application and the available of accounting information at small and medium enterprises in Pekanbaru City. The population this research is small and medium enterprises in Pekanbaru City. Sampling method on this study uses a Simple Random Sampling method targeted to 100 small and medium enterprises in Pekanbaru City with error level of 10%. Data were collected through questionnaires targeted to manager/owner’s of small and medium enterprises. Data analysis techniques used in the study are double linear regression analysis. This study concludes that manager/owner’s educational background, and training on accounting effect on application and available of accounting information. Business size, length of time in managing, and business age are not effect on application and available of accounting information on small and medium enterprises in Pekanbaru City.Keywords: accounting information, small and medium enterprises